The Childfree Choice and Female Labor Market Participation: Evidence from Indonesia - Oktabriyantina, Wulan (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study explores the relationship between childfree status and women’s labor force participation in Indonesia, using data from the March 2023 Susenas. The childfree group—defined as women who have never given birth, are not pregnant, and use contraception—comprises only 917 women (0.07% of the sample), primarily urban, educated, and of working age. Using binary logistic regression, the analysis reveals that childfree women are more likely to participate in the labor market, especially those who have never married. Although the association is only marginally significant, the trend suggests that fertility preferences may influence economic behavior. Despite the small sample, these findings provide early evidence of shifting norms among Indonesian women and emphasize the need for inclusive labor and social policies that acknowledge diverse life choices. The study adds to the limited literature on voluntary childlessness in developing countries and encourages broader discussions on gender, fertility, and employment.